Estudo comparativo de respostas da banana às aplicações de fertilizante mineral e biofertilizante na Chapada do Apodi - CE. - Santos, José Wilson Gomes dos (2011)
The liquid biofertilizers have been used with relative success in the recovery of banana plantations that have low productivity due to long time of cultivation. The area of the present study needs further investigations because there is little information available related to the cultural practices that could increase the time of the crop yield. The objective of the present study was to compare the areas of degraded banana plantations that received application of fertilizer for a period of 2 e 5 years with the areas where the crop did not receive fertilizer application. It was studied the effects of time of application on soil chemical characteristics, biometric measurements of the plant (height, number, length and width of leaves), dry matter production, extraction and export of N, P and K by the plants ( the mother, the daughter and the granddaughter banana plants) and amount of incorporated of plant residues into the soil. The studies were conducted in the localities of Frutacor. and Damami Farms Ltd at the Apodi plateau (county of Quixeré-CE, Brazil), where three areas were selected with commercial production of banana. The areas were: 1) - a control area (CA) irrigated with river water and using only mineral fertilizer; 2) - an area that received biofertilizer applications during two years plus mineral fertilization (A2) and being irrigated with well water; and 3) - another area that received 5 years of biofertilizer application plus mineral fertilization (A5) also irrigated with well water. All these areas were planted with banana Pacovan for 13 consecutive years of cultivation following a planting spacing with double rows and density of 1400 plants per hectare. The experimental design was a completely randomized blocks with three replications. The biofertilizer application increased the content of organic matter, exchangeable Ca and K contents in the three soil depths. The levels of extractable P and exchangeable Mg contents were higher only at the surface layer. The irrigation with well water and application of biofertilizer increased soil pH, soil EC and soil Na. Plants that received application of biofertilizer were higher, with both greater weight and number of leaves. The A5 area that has received the application of biofertilizer for more time showed higher productivity, accumulated 20% more dry matter than the control area, extracted more N, P and K from soil, exported more nutrients through harvesting and deposited larger amounts or plant residues on the soil. Key words: Banana; Biofertilizer; Extraction of Nutrients.